(untitled) (Research, Society and Development, 2023)
Cocoa (Theobroma cacao L.) holds significance in the commercial market and the chocolate production industry. In Brazil, cocoa trees are extensively cultivated in the Northern region, with emphasis on the state of Pará, where cocoa from the floodplain islands of Lower Tocantins is influenced by natural factors and traditional cultivation practices. To obtain cocoa by-products, certain procedures are conducted. The drying stage is crucial in this process to ensure food stability by reducing water content. Drying can occur naturally on raised platforms or artificially in a vertical dryer with induced forced air. The present study aimed to analyze the kinetics of different types of drying of native cocoa almonds from the floodplain islands of Lower Tocantins. The almonds were subjected to specific treatments, including a dryer silo with heated air at 60°C (T1), a dryer silo without heated air (T2), and drying on raised platforms (T3). Additionally, different mathematical models were fitted to the processes. The Henderson and Pabis, Valcam, and Page models provided the best fits for the experimental data of treatments T1 (dryer silo with heated air at 60°C), T2 (dryer silo without heated air), and T3 (raised platforms), respectively. The drying rates were 3.9%, 1.9%, and 3.9% for treatments T1, T2, and T3, respectively, indicating the influence of drying time and temperature on almond drying rate. These findings help comprehend the cocoa almond drying process, enhancing their utilization in the production of quality by-products such as chocolate.